2009
DOI: 10.1111/j.1399-3038.2008.00834.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of parental educational level on the development of atopic sensitization, wheezing and eczema during the first year of life

Abstract: Several studies have investigated the association between socioeconomic status and the occurrence of allergies. Nevertheless, the results remain contradictory. The aim of this study was to evaluate the associations between parental education and the occurrence of atopic sensitization, recurrent wheezing and eczema during the first year of life, differentiating between atopic and non-atopic disorders based on specific serum IgE. We conducted an aetiological study in 690 children, based on a prospective birth co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
3
14
1
Order By: Relevance
“…We found children were less likely to belong to the "nonatopic, asthma and rhinitis" phenotype at 1.5 years if they were breastfed for â©Ÿ6 months or had better educated parents and were more likely to belong to this phenotype if they had older siblings or mothers who smoked in pregnancy. These findings are consistent with previous reports on risk factors for early life wheezing illness [38,41,42]. Our results support studies that have found that eczema in early life is a risk factor for asthma in later childhood [43].…”
Section: Discussionsupporting
confidence: 94%
“…We found children were less likely to belong to the "nonatopic, asthma and rhinitis" phenotype at 1.5 years if they were breastfed for â©Ÿ6 months or had better educated parents and were more likely to belong to this phenotype if they had older siblings or mothers who smoked in pregnancy. These findings are consistent with previous reports on risk factors for early life wheezing illness [38,41,42]. Our results support studies that have found that eczema in early life is a risk factor for asthma in later childhood [43].…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, it could be considered that higher educated parents tend to be more worried about their childrenÕs health than less educated (7,39). We hypothesize that the fact that AD is more closely related to maternal than paternal education (also found by Dom et al,50) is caused by the fact that well-educated mothers are better able to interpret possible symptoms of AD, and it is mothers who more likely have filled in the questionnaire.…”
Section: Resultsmentioning
confidence: 82%
“…Eczema phenotypes that take into account the age of onset and persistence over time may enable better identification of specific environmental exposures and genetic mechanisms that might play a role in the development of eczema . Previous studies suggest that higher maternal education, non‐European ethnicity, having older siblings, shorter duration or nonexclusivity of breastfeeding, day care attendance and no pet exposure are associated with an increased risk of childhood eczema . In addition, loss‐of‐function mutations in the gene encoding filaggrin ( FLG ), an indispensable protein for epidermal differentiation and maintenance of an optimal skin barrier, are well known to be associated with eczema .…”
mentioning
confidence: 99%